Spontaneous Coronary Artery Dissection (SCAD): FEMALE SURVIVORS' EXPERIENCES OF STRESS AND SUPPORT. Issue 6 (November 2018) - Wagers, Tina Pittman; Stevens, Courtney J.; Ross, Kaitlin V.; Leon, Katherine Kelly; Masters, Kevin S.
Abstract : Purpose: Spontaneous coronary artery dissection (SCAD) is a nonatherosclerotic type of acute myocardial infarction that primarily affects young, healthy women without typical risk factors for heart disease. Few investigations have examined psychosocial variables in this population and none have looked at patient perceptions of the experience and stresses associated with having a SCAD event or the resources currently available to SCAD survivors. This investigation describes survivors' subjective experiences of SCAD. Participants also provided information about types and helpfulness of resources available to them post-SCAD, including cardiac rehabilitation. Methods: Participants were recruited online and completed a one-time questionnaire. Results: Participants (n = 409) completed a questionnaire concerning their experiences with their SCAD event in the 1 y and 2 wk prior to the SCAD event. Their responses reflected moderate to high perceptions of stress. Participants experienced the SCAD event as highly stressful and frightening and their heart health presents as a moderate-severe source of current, post-diagnosis stress. Spontaneous coronary artery dissection–based informational support was frequently rated as inadequate, whereas other supportive resources varied in their helpfulness and accessibility. Participants reported positive experiences in cardiac rehabilitation and strong interest in SCAD-specific, professionally led, online patient education and support groups. Conclusions: This study is the largest to date investigation of SCAD survivors and their experiences in this understudied and perhaps underrecognized condition. Opportunities for researchers and providers to develop, tailor, and disseminate SCAD-specific interventions are discussed. Abstract : Supplemental Digital Content is Available in the Text.Spontaneous coronary artery dissection (SCAD) is a nonatherosclerotic type of acute myocardial infarction that primarily affects young, healthy women. This study reports on a survey of attitudes about psychosocial variables and resources in SCAD survivors (n = 409). Implications for cardiac rehabilitation providers delivering services to SCAD survivors are discussed.